A two step hydrothermal process to prepare carbon spheres from bamboo for construction of core–shell non-metallic photocatalysts12. (3rd April 2018) - Wang, Tao; Liu, Xiqing; Ma, Changchang; Liu, Yang; Dong, Hongjun; Ma, Wei; Liu, Zhi; Wei, Maobin; Li, Chunxiang; Yan, Yongsheng
Abstract : Carbon spheres were prepared by a two step hydrothermal method from bamboo, both as electron receivers and electron donors. Abstract : This work reports the direct transformation of the biomass of bamboo into carbon spheres by two step hydrothermal carbonization (HTC) at 180–200 °C. Such carbon spheres have potential applications as electrode materials with excellent electrical conductivity and high chemical stability. The biochar spheres (BS) were modified via protonation of g-C3 N4 to form non-metallic photocatalysts with a unique core–shell architecture. In the BS@g-C3 N4 core–shell photocatalysts, the protonated g-C3 N4 sheets were the main photocatalyst and the biochar spheres acted both as a reservoir and a sensitizer, and displayed outstanding light absorption in nearly the entire wavelength range, due to the narrower gap of the sp 2 carbon cluster and large amounts of carbon clusters. Conversion of raw biomass into stable carbon materials under relatively mild conditions offers a promising route to overcoming the challenges in obtaining biochar materials with precisely controlled morphology. Building a green non-metallic photocatalyst is an environmentally friendly embodiment of this.